2008
DOI: 10.1097/ijg.0b013e3181507313
|View full text |Cite
|
Sign up to set email alerts
|

Bimatoprost/Timolol Fixed Combination: A 3-month Double-masked, Randomized Parallel Comparison to Its Individual Components in Patients With Glaucoma or Ocular Hypertension

Abstract: FC was statistically significantly more effective than BIM or TIM for most comparisons, and safer than BIM with respect to common ocular adverse events. FC represents a convenient, therapeutic advantage over separate bottles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 15 publications
4
47
2
9
Order By: Relevance
“…Ressalta-se, todavia, o fato de as aferições não terem sido realizadas todas no mesmo horário do dia. Média (dp) Dentre os pacientes estudados, 17 (26,6%) apresentaram queixa de hiperemia conjuntival, incidência esta menor do que o encontrado por Brandt et al (18) , em cujo estudo achou-se 38,5% de ocorrência. Não foi observado crescimento dos cílios, sendo que isto pode se dever ao fato de os pacientes terem sido acompanhados por apenas 1 mês, tempo inferior ao encontrado na literatura para a observação do efeito (19)(20)(21) .…”
Section: Discussionunclassified
“…Ressalta-se, todavia, o fato de as aferições não terem sido realizadas todas no mesmo horário do dia. Média (dp) Dentre os pacientes estudados, 17 (26,6%) apresentaram queixa de hiperemia conjuntival, incidência esta menor do que o encontrado por Brandt et al (18) , em cujo estudo achou-se 38,5% de ocorrência. Não foi observado crescimento dos cílios, sendo que isto pode se dever ao fato de os pacientes terem sido acompanhados por apenas 1 mês, tempo inferior ao encontrado na literatura para a observação do efeito (19)(20)(21) .…”
Section: Discussionunclassified
“…15 Çoklu ilaç kullanımıyla sabit kombinas yon tedavilerinin etkinliğinin karşılaştırıldığı birçok çalışma yapılmış-tır. [16][17][18][19] TDSK ve bileşenlerinin değerlendirildiği bir çalışmada, sabit kombinasyonun bileşen maddelerinin ayrı ayrı kullanımından daha etkin olduğu gösterilmiştir. 16 TBSK ve bileşen maddelerinin ayrı ayrı etkilerinin karşılaştırıldığı bir çalışmada ise GİB üzerindeki düşürücü etkilerinin benzer olduğu, ancak sabit kombinasyonun ayrı kullanıma göre konjonktival hiperemiye daha az neden olduğu ve bunun ayrı kullanıma göre bir üstünlük sağladığı bildirilmiştir.…”
Section: Bulgularunclassified
“…17 Öte yandan prostaglandin analoglarının timolol ile sabit kombinasyonları ile ayrı ayrı kullanımlarının karşılaştırıldığı bir çalış-mada, timolol-bimatoprost, timolol-latanoprost ve timolol-travaprost sabit kombinasyonları değer-lendirilmiş ve bu üç kombinasyonun diurnal dalgalanma ve GİB kontrolünün bileşenlerinin ayrı kullanımından daha iyi olduğu sonucuna varılmış-tır. 18,19 Kombine tedavide farklı reseptörler üzerinden etki gösteren ya da farklı etki mekanizması olan ilaçlar tercih edilmelidir. Nonselektif bir beta blokör olan timolol aköz üretimini azaltarak ve aköz dışa akımını artırarak etki etmektedir.…”
Section: Bulgularunclassified
“…16 mmHg) on mono-or dual therapy had lower diurnal IOP with FCLT (16.9 mmHg) than concomitant brimonidine and timolol (18.2 mmHg), P , 0.001, at 6 months, 156 also supported by a cross-over study with a 1-month timolol run-in period. 154 Data from 3 Phase III clinical studies 199,200 have shown that the fixed combination of bimatoprost 0.03%/timolol 0.5% (FCBT) ophthalmic solution (Ganfort ® ; Allergan inc., Irvine, CA) was significantly more effective in lowering IOP, with a higher percentage achieving mean reduction in diurnal IOP of .20% or a target pressure of ,18 mmHg, than timolol or bimatoprost monotherapy. From the pooled analysis of 2 trials, 199 mean reduction in IOP from baseline was 7.4 to 9.6 mmHg in the FCBT group, 6.7 to 8.8 mmHg in the bimatoprost group, and 5.2 to 7.4 mmHg in the timolol treated group.…”
Section: Pga/timolol Fixed Combinationsmentioning
confidence: 99%
“…154 Data from 3 Phase III clinical studies 199,200 have shown that the fixed combination of bimatoprost 0.03%/timolol 0.5% (FCBT) ophthalmic solution (Ganfort ® ; Allergan inc., Irvine, CA) was significantly more effective in lowering IOP, with a higher percentage achieving mean reduction in diurnal IOP of .20% or a target pressure of ,18 mmHg, than timolol or bimatoprost monotherapy. From the pooled analysis of 2 trials, 199 mean reduction in IOP from baseline was 7.4 to 9.6 mmHg in the FCBT group, 6.7 to 8.8 mmHg in the bimatoprost group, and 5.2 to 7.4 mmHg in the timolol treated group. Some subjects were unresponsive to timolol prior to the study and one study had a run-in period of timolol twice daily.…”
Section: Pga/timolol Fixed Combinationsmentioning
confidence: 99%